2010
DOI: 10.1007/s00442-010-1676-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatially complex neighboring relationships among grassland plant species as an effective mechanism of defense against herbivory

Abstract: Close spatial relationships between plant species are often important for defense against herbivory. The associational plant defense may have important implications for plant community structure, species diversity, and species coexistence. An increasing number of studies have focused on associational plant defense against herbivory at the scale of the individual plant and its nearest neighbors. However, the average neighborhood effects between plant species at the scale of whole plant communities have received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 41 publications
2
51
0
Order By: Relevance
“…The difference in plant species diversity is a typically important characteristic of heterogeneity, and diverse plant communities can markedly affect foraging strategies of large herbivores and their concomitant impacts on the dynamics of vegetation itself (Bergvall et al, 2006;Miller et al, 2007;Wang et al, 2011). Our previous work found that complex spatial neighborhood of several plant species makes the palatable species for herbivores to less selected, contributing to the maintenance of plant diversity (Wang et al, 2010). This 'plant species diversity disaffinity' may be an important factor influencing subsequent herbivores' impacts on plant community, which, in turn, consequently impacts insect community.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in plant species diversity is a typically important characteristic of heterogeneity, and diverse plant communities can markedly affect foraging strategies of large herbivores and their concomitant impacts on the dynamics of vegetation itself (Bergvall et al, 2006;Miller et al, 2007;Wang et al, 2011). Our previous work found that complex spatial neighborhood of several plant species makes the palatable species for herbivores to less selected, contributing to the maintenance of plant diversity (Wang et al, 2010). This 'plant species diversity disaffinity' may be an important factor influencing subsequent herbivores' impacts on plant community, which, in turn, consequently impacts insect community.…”
Section: Introductionmentioning
confidence: 99%
“…It was a big challenge to predict that the heterogeneity of grasshopper patches are critical factors that influenced by foraging selectivity and habitat heterogeneity.This study finds that grasshopper population was good at selecting a micro-environment to a dwelling. The semivariable function of grasshopper abundance and vegetation community were a nonlinear model in geostatistics; while in ecology, the curves meant that the spatial distribution pattern was aggregated (Wang, et al 2010;Zhong, et al 201r). The grasshopper abundance typically produces spacial heterogeneity with larger range and nuggets than vegetation community (except the range of vegetation coverage in model).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…L. chinensis is a perennial rhizomatous grass with good palatability and high forage value [8], [40], [41], [42], [43], [44]. It is widely distributed in the eastern region of the Eurasian steppe zone as a dominant species from arid to semi-arid steppes in northern China and eastern Mongolia, and it has extensive plasticity in morphological and physiological characteristics.…”
Section: Methodsmentioning
confidence: 99%